The Educational dimensions of children's television programs in the light of the universal rights of child (Journal Of Educational and Psychological Researches, 2022)
The research aims at determining the type of educational dimensions to be broadcasted in children's television programs, clarifying the technical forms used in children's TV programs, analyzing the educational dimensions provided by children's television programs, and studying the educational dimensions of children's television programs. The researcher used a sample of children's programs: all of us heroes, which is a daily program on the mbc3 channel as well as the program of Tel flowers on the Algerian channel. The researcher designed an analysis content form included categories of analysis. Spss program was used to process the collected data. The research reached several results; the concentration of educational dimensions in the children's programs is on moral and educational behaviors, as they are the most important things that the child should learn. The learning and knowledge are the most educational dimensions focused on the children's programs as well as helping others and caring for cleanliness, and the majority of children's programs focus on the educational and instructional goals.